Tumour necrosis factor-α and adenosine in endotoxin shockleading related cardiovascular symptoms - S. Sipka; T. Seres; Z. Dinya; Z. Szekanecz; J. Szentmiklósi; E. Bodolay; G. Szegedi (Mediators of Inflammation)
We have observed uncontrollable cardiogenic shock as a cardiovascular manifestation of systemic inflammatory response syndrome (SIRS) leading to death in a 62-year-old woman. The diagnosis of SIRS was based on the demonstration of endotoxinaemia, and highly elevated plasma levels of tumour necrosis factor (TNF)-α, and interleukin (IL)-10. We suggest that these cytokines may contribute to the terminal SIRS-related arrythmias, impaired myocardial contractility, as well as increased vascular permeability. In addition, the increased production of adenosine, a counter-regulatory mediator of inflammation, may also play a role in cardiodepression. We suggest a relationship between the action of TNF-α , IL-10 and adenosine in the pathogenesis of circulatory symptoms described above.